Steel for torsion beam and preparation method thereof

By designing specific chemical composition and microstructure structures, combining calcium treatment and refining processes, the problem of poor forming performance of torsion beam steel in the prior art is solved, and steel for torsion beam with high strength, excellent forming performance and welding performance is achieved.

CN119640148AActive Publication Date: 2025-03-18SHOUGANG GROUP CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411825927.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

It is difficult to obtain steel for high-strength torsion beams with high forming performance in the prior art.

Method used

By designing specific chemical components, including C, Si, Mn, P, S, Nb, Ti, Cr, Mo, V, Ca and Fe, ensure [Ti]/[Mo]≤0.6 and [Cr]+[Mo]=0.2%-0.5%, the microstructure of ferrite and bainite is formed, the grain size is refined, and the forming performance of steel for torsion beams is improved through calcium treatment and refining processes.

Benefits of technology

On the basis of ensuring strength, it is achieved to improve the forming performance and welding performance of torsion beam steel, meet the requirements of high tensile strength, pore reaming and elongation, and ensure excellent surface quality and welding properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640148A_ABST
    Figure CN119640148A_ABST
Patent Text Reader

Abstract

The invention relates to steel for a torsion beam and a preparation method of the steel. The steel comprises the following chemical components: 0.05 to 0.08 percent of C, less than or equal to 0.15 percent of Si, 1.2 to 1.7 percent of Mn, less than or equal to 0.015 percent of P, less than or equal to 0.003 percent of S, 0.01 to 0.05 percent of Nb, 0.03 to 0.08 percent of Ti, 0.1 to 0.4 percent of Cr, 0.1 to 0.25 percent of Mo, 0.01 to 0.04 percent of V, 0.0005 to 0.005 percent of Ca and the balance of Fe. [Ti] / [Mo] < = 0.6, and [Cr] + [Mo] = 0.2-0.5%; the microstructure of the steel for the torsion beam comprises ferrite and bainite. The steel for the torsion beam has the advantages that the tensile strength is larger than or equal to 650 MPa, the hole expansion rate lambda is larger than or equal to 85%, and the ductility A80 is larger than or equal to 24%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel preparation, and in particular to a steel for a torsion beam and a preparation method thereof. Background Art

[0002] As an important part of the passenger car chassis structure, the torsion beam is particularly suitable for use in compact passenger cars and new energy vehicles because of its simple structure, space saving, low manufacturing cost and easy maintenance.

[0003] In order to achieve the goal of lightweight and improved service performance, the torsion beam design has evolved from U / V torsion beams to tubular torsion beams; at the same time, in order to improve production efficiency and shorten the production process, high-frequency resistance welded tubes for torsion beam crossbeams + no subsequent annealing process are often used. However, it is difficult to obtain high-strength torsion beam steel with high formability. Summary of the invention

[0004] The present application provides a torsion beam steel and a preparation method thereof to solve the following technical problem: how to improve the forming performance of the torsion beam steel.

[0005] In a first aspect, the present application provides a torsion beam steel, the chemical composition of the torsion beam steel comprising:

[0006] C, Si, Mn, P, S, Nb, Ti, Cr, Mo, V, Ca and Fe; wherein, by mass fraction, the content of C is 0.05-0.08%, the content of Si is ≤0.15%, the content of Mn is 1.2-1.7%, the content of P is ≤0.015%, the content of S is ≤0.003%, the content of Nb is 0.01-0.05%, the content of Ti is 0.03-0.08%, the content of Cr is 0.1%-0.4%, the content of Mo is 0.1-0.25%, the content of V is 0.01-0.04%, and the content of Ca is 0.0005-0.005%;

[0007] And satisfying [Ti] / [Mo]≤0.6, [Cr]+[Mo]=0.2%~0.5%,

[0008] Wherein, [Ti] represents the mass fraction of Ti, [Mo] represents the mass fraction of Mo, and [Cr] represents the mass fraction of Cr;

[0009] The microstructure of the torsion beam steel includes ferrite and bainite, wherein the bainite includes granular bainite and lath bainite, wherein, in terms of area fraction,

[0010] The content of ferrite is ≥50%, the content of granular bainite is 20% to 35%, and the content of lath bainite is ≤10%.

[0011] Optionally, the C content is 0.072% to 0.076%, the Si content is 0.08% to 0.12%, the Mn content is 1.22% to 1.65%, the Nb content is 0.0251% to 0.0252%, the Ti content is 0.042%, the Cr content is 0.23% to 0.37%, the Mo content is 0.11% to 0.12%, the V content is 0.012% to 0.028%, and the Ca content is 0.002%.

[0012] Optionally, the welding sensitivity coefficient Pcm≤0.18%.

[0013] Optionally, the equivalent grain size in the microstructure is 2.5 μm to 5 μm.

[0014] Optionally, the torsion beam steel meets the following properties: tensile strength ≥ 650 MPa, hole expansion rate λ ≥ 85%, elongation A80 ≥ 24%, and surface quality FB grade.

[0015] In a second aspect, the present application provides a method for preparing the torsion beam steel according to any one of the embodiments of the first aspect, the method comprising:

[0016] The molten iron is pre-treated, then smelted, calcium treated and continuously cast to obtain a slab;

[0017] The slab is heated and rolled, and then cooled and coiled to obtain steel for a torsion beam; wherein the coiling temperature is 520°C to 600°C.

[0018] Optionally, the coiling temperature is 560°C to 580°C.

[0019] Optionally, the heating temperature is 1230°C to 1280°C.

[0020] Optionally, the rolling includes rough rolling and finish rolling, wherein the end temperature of the rough rolling is 1050°C to 1100°C, and the end temperature of the finish rolling is 830°C to 900°C.

[0021] Optionally, the method further includes:

[0022] The torsion beam steel is flattened and then pickled to obtain a torsion beam steel finished product; wherein,

[0023] The flattening elongation is 1% to 3%, and the pickled strip steel running speed is 60m / min to 100m / min.

[0024] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0025] The torsion beam steel provided in the embodiment of the present application has a chemical composition in which the C content ensures the material's formability and welding performance while ensuring strength; the Mn content effectively plays a role in solid solution strengthening and grain refinement strengthening; the S and P contents are at a relatively low level, reducing the brittleness of the material and improving the formability; the Si content plays a role in solid solution strengthening in the steel, and the Si content inhibits the precipitation of carbides and delays the formation of pearlite; the Ni content and the V content can play a role in grain refinement and precipitation strengthening; the Ti content plays a role in nitrogen fixation and combines with free nitrogen atoms in the steel to form TiN, and the TiC and Ti(C,N) formed during the welding process of high-strength steel can play a role in grain refinement, and the precipitates can also inhibit the precipitation of cementite during the phase transformation process, and promote the carbon element in the two-phase region after cooling after rolling. The Cr content can delay the pearlite transformation and expand the bainite transformation zone. The Mo content can improve the hardenability of the steel and achieve the regulation of the ferrite-bainite structure. On the other hand, it forms a dispersed stable precipitation during the cooling process after rolling to improve the strength and welding performance. Ni and V can refine the grains and strengthen the steel through precipitation. The Ca content can reduce the oxide inclusions in the steel and purify the steel. Limiting [Ti] / [Mo] can make Mo and Ti combine to form fine dispersed precipitation. Limiting the value of [Cr]+[Mo] can achieve high hardenability and precipitation strengthening. The content of the above chemical elements is comprehensively designed to regulate the ideal microstructure of ferrite+bainite and refine the grain size of the structure, thereby improving the forming performance of the torsion beam steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0028] Figure 1 A microstructure diagram of a torsion beam steel provided according to some embodiments of the present application;

[0029] Figure 2 A schematic flow chart of a method for preparing steel for a torsion beam according to some embodiments of the present application. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0032] In this application, the terms "including", "comprising", etc. mean "including but not limited to".

[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0034] The present application provides a torsion beam steel, the chemical composition of the torsion beam steel comprising:

[0035] C, Si, Mn, P, S, Nb, Ti, Cr, Mo, V, Ca and Fe; among them, in terms of mass fraction,

[0036] The content of C is 0.05-0.08%, the content of Si is ≤0.15%, the content of Mn is 1.2-1.7%, the content of P is ≤0.015%, the content of S is ≤0.003%, the content of Nb is 0.01-0.05%, the content of Ti is 0.03-0.08%, the content of Cr is 0.1%-0.4%, the content of Mo is 0.1-0.25%, the content of V is 0.01-0.04%, and the content of Ca is 0.0005-0.005%;

[0037] And satisfying [Ti] / [Mo]≤0.6, [Cr]+[Mo]=0.2%~0.5%,

[0038] Wherein, [Ti] represents the mass fraction of Ti, [Mo] represents the mass fraction of Mo, and [Cr] represents the mass fraction of Cr;

[0039] The microstructure of the torsion beam steel includes ferrite and bainite, wherein the bainite includes granular bainite and lath bainite. Figure 1 A microstructure diagram of a torsion beam steel provided according to some embodiments of the present application; see Figure 1 , where, in terms of area fraction,

[0040] The content of ferrite is ≥50%, the content of granular bainite is 20% to 35%, and the content of lath bainite is ≤10%.

[0041] In some embodiments, the C content is 0.072% to 0.076%, the Si content is 0.08% to 0.12%, the Mn content is 1.22% to 1.65%, the Nb content is 0.0251% to 0.0252%, the Ti content is 0.042%, the Cr content is 0.23% to 0.37%, the Mo content is 0.11% to 0.12%, the V content is 0.012% to 0.028%, and the Ca content is 0.002%.

[0042] C is an austenite element that can improve the stability of austenite. The carbon content determines the strength of the steel plate to a large extent. In the embodiment of the present application, C not only forms microalloy precipitation through solid solution strengthening and precipitation strengthening to improve the strength, but C is also a very important indicator affecting the carbon equivalent. When the mass fraction of C is too high, the material strength will be too high and the carbon equivalent will be too high, affecting the material's forming performance and welding performance; when the mass fraction of C is too low, it is difficult to form enough microalloy precipitation to ensure the material strength. Exemplarily, the above-mentioned C content can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, etc.

[0043] Si has a certain solid solution strengthening effect in steel. Si delays the formation of pearlite by inhibiting the precipitation of carbides. When the mass fraction of silicon is too high, red iron scale will form on the surface of the steel after rolling, which will deteriorate the surface quality after pickling and is not conducive to pipe making and forming. For example, the above-mentioned Si content can be 0.15%, 0.14%, 0.13%, 0.12%, etc.

[0044] Mn is an austenite stabilizing element, which improves the hardenability of steel, delays pearlite transformation and reduces bainite transformation temperature, refines the organizational substructure of steel and has a certain solid solution strengthening effect. When the mass fraction of Mn is too high, it will lead to a decrease in plasticity and easily form segregation and MnS inclusions, thereby affecting the performance stability and fatigue performance of pipe strips; when the mass fraction of manganese is too low, it is difficult to effectively play the role of solid solution strengthening and fine grain strengthening, resulting in insufficient strength. Exemplarily, the above-mentioned Mn content can be 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, etc.

[0045] Phosphorus in steel is generally dissolved in ferrite and has a strong solid solution strengthening effect, which is used to increase the strength of steel and reduce the toughness of steel. However, excessive Phosphorus content will cause phosphorus segregation, resulting in a decrease in grain boundary strength and affecting strength and welding performance. For example, the Phosphorus content can be 0.015%, 0.013%, 0.011%, 0.009%, etc.

[0046] The S content and the morphology of sulfides are the main factors affecting formability and fatigue performance. The more sulfides there are and the larger the size of the inclusion sulfides, the more unfavorable it is to the plasticity and the fatigue performance will be deteriorated. For example, the S content can be 0.003%, 0.0025%, 0.002%, etc.

[0047] Nb is an important precipitation and grain refinement element. It has a strong inhibitory effect on the recrystallization of deformed austenite during rolling. Nb can increase the recrystallization temperature. At the same time, it forms tiny carbonitrides during cooling to precipitate and improve strength and toughness, which has a positive effect on improving formability and fatigue performance. When the mass fraction of Nb is too high, the plasticity of the steel will decrease. When the mass fraction of Nb is too low, it is difficult to play the role of grain refinement and precipitation strengthening. Exemplarily, the above-mentioned Nb content can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, etc.

[0048] Ti is one of the important precipitation strengthening and fine grain strengthening elements. In the embodiments of the present application, Ti plays a nitrogen fixing role on the one hand and combines with free nitrogen atoms in steel to form TiN. On the other hand, a small amount of titanium forms TiC and Ti(C,N) during the welding process of high-strength steel, which can play a role in grain refinement. At the same time, the precipitate can also inhibit the precipitation of cementite during the phase transformation process, and promote the carbon element to achieve strength improvement and inhibit welding softening effect in the two-phase region after rolling cooling. When the mass fraction of Ti is too large, large-sized TiN will be formed, which will deteriorate the fatigue performance and cause the process window to be too narrow, resulting in incompatible performance; when the mass fraction of Ti is too low, it is difficult to play a role in grain refinement and precipitation strengthening. Exemplarily, the above-mentioned Ti content can be 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, etc.

[0049] Cr has the function of delaying pearlite transformation and expanding bainite transformation zone, improving strength and expanding process window. Usually, the Cr content must be greater than 0.1% to significantly delay the formation of pearlite, so as to achieve reasonable regulation of the volume fraction of ferrite and bainite. In the embodiment of the present application, Cr can replace part of the role of Si element without causing surface deterioration. When the mass fraction of chromium is too large, it will lead to excessive bainite content, insufficient forming performance, and easy to form segregation and deteriorate fatigue performance; when the mass fraction of chromium is too low, it is difficult to improve hardenability and delay the formation of pearlite. Exemplarily, the above Cr content can be 0.1%, 0.2%, 0.3%, 0.4%, etc.

[0050] Mo can improve the hardenability of the material, achieve ferrite bainite structure control, and form dispersed stable precipitation during the cooling process after rolling to improve strength and welding performance. When the mass fraction of Mo is too high, it will lead to increased costs; when the mass fraction of Mo is too low, it is difficult to improve hardenability and precipitation strengthening. Exemplarily, the above-mentioned Mo content can be 0.1%, 0.2%, 0.25%, etc.

[0051] V improves strength and improves fatigue properties of materials through precipitation strengthening and microstructure refinement. When the mass fraction of V is too high, it will lead to the appearance of aggregated carbides, which will reduce strength and deteriorate forming properties; when the mass fraction of V is too low, it is difficult to play the role of precipitation strengthening and improving welding properties. Exemplarily, the above-mentioned V content can be 0.01%, 0.02%, 0.03%, 0.04%, etc.

[0052] Ca is an important element for improving fatigue performance in the embodiments of the present application. Calcium treatment can reduce oxide inclusions in steel, purify steel, and control the morphology and quantity of inclusions, which is beneficial to improving the material forming ability and fatigue performance. When the mass fraction of calcium is too high, it will cause an increase in inclusions and deteriorate the performance. When the mass fraction of calcium is too low, it is difficult to achieve the effect of calcium treatment on inclusion modification. Exemplarily, the above-mentioned Ca content can be 0.005%, 0.007%, 0.009%, 0.0005%, 0.0007%, 0.0009%, 0.001%, 0.002%, 0.003%, 0.004%, etc.

[0053] Limiting the value of [Ti] / [Mo] can further promote the fineness of precipitates, improve the uniformity of the structure and fatigue performance. For example, the above [Ti] / [Mo] can be 0.6, 0.5, 0.4, 0.3, etc.

[0054] The value of [Cr]+[Mo] is limited. Cr and Mo can jointly achieve the effects of high hardenability and precipitation strengthening. When the sum of the mass percentages is too high, the plasticity of the steel will be too poor, and it will be difficult to meet the requirements of the bainite-ferrite structure component; when the sum of the mass percentages is too low, the material strength will be too low to meet the requirements. For example, the value of [Cr]+[Mo] can be 0.2%, 0.3%, 0.4%, 0.5%, etc.

[0055] As some of the embodiments, the C content may be 0.072% to 0.076%, the Si content may be 0.08% to 0.12%, the Mn content may be 1.22% to 1.65%, the Nb content may be 0.0251% to 0.0252%, the Ti content may be 0.042%, the Cr content may be 0.23% to 0.37%, the Mo content may be 0.11% to 0.12%, the V content may be 0.012% to 0.028%, and the Ca content may be 0.002%.

[0056] Figure 1 A microstructure diagram of a torsion beam steel provided according to some embodiments of the present application; see Figure 1 , limiting the area fractions of ferrite, lath bainite and granular bainite, can not only achieve the 650MPa tensile strength requirement, but also meet the high formability requirement. Exemplarily, the content of the ferrite is 50%, 52%, 54%, 56%, 58%, 60%, etc., the content of the granular bainite is 20%, 25%, 30%, 35%, etc., and the content of the lath bainite is 10%, 9%, 8%, 7%, etc.

[0057] In some embodiments, the equivalent grain size in the microstructure is 2.5 μm to 5 μm.

[0058] In the embodiment of the present application, the metallographic structure of the steel for the torsion beam is composed of fine-grained ferrite and bainite, and the equivalent grain size in the structure is 2.5μm to 5μm. The bainite structure is uniform and has good formability. During the bench test, due to the uniformity of the structure, it is not easy to generate stress concentration and cracks in the steel, thereby ensuring that it has good fatigue performance. Exemplarily, the equivalent grain size in the above microstructure can be 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5μm, etc. Definition of equivalent grain size (d): Where A is the grain area.

[0059] In some embodiments, the welding sensitivity coefficient Pcm≤0.18%.

[0060] In the embodiment of the present application, the welding sensitivity coefficient Pcm=([C]+[Si] / 30+[Mn] / 20+[Mo] / 15+[Cr] / 20+[V] / 10)≤0.18%. The smaller this coefficient is, the better the welding performance of the steel is. The welding sensitivity coefficient ≤0.18% indicates that the material has excellent welding performance. For example, the welding sensitivity coefficient Pcm can be 0.18%, 0.17%, 0.16%, etc.

[0061] In some embodiments, the torsion beam steel meets the following properties: tensile strength ≥ 650 MPa, hole expansion rate λ ≥ 85%, elongation A80 ≥ 24%, and surface quality of FB grade.

[0062] In the embodiment of the present application, the above-mentioned torsion beam steel meets the following properties: tensile strength ≥ 650MPa, hole expansion rate λ ≥ 85%, elongation A80 ≥ 24%, and surface quality is FB grade (good and above).

[0063] Figure 2 A schematic diagram of a process for preparing a torsion beam steel according to some embodiments of the present application; see Figure 2 The present application provides a method for preparing the torsion beam steel according to any one of the embodiments of the first aspect, the method comprising:

[0064] S1, pre-treating molten iron, then smelting, calcium treatment and continuous casting to obtain slabs;

[0065] In the embodiment of the present application, the above-mentioned smelting includes converter smelting, LF refining and RH refining. The above-mentioned calcium treatment can feed 450m to 550m of wire per furnace, which achieves the effect of fine-tuning the composition of molten steel and modifying inclusions. If the wire feeding amount is too low, it is not possible to effectively remove oxide inclusions and achieve pure steel; if the wire feeding amount is too high, it is difficult to obtain the target composition. Since the cleanliness of the molten steel is improved by calcium treatment of the molten steel after the refining, the pulling speed is controlled at 1.0 to 1.2m / min and the superheat is 40 to 60°C during the continuous casting process, and the full protection casting with high superheat and low pulling speed is used to improve the castability of the molten steel, ensure the cleanliness of the molten steel, and ensure the uniformity of the ingot structure.

[0066] S2. Heating and rolling the slab, and then cooling and coiling it to obtain steel for a torsion beam; wherein the coiling temperature is 520°C to 600°C.

[0067] In some embodiments, the coiling temperature is 560°C to 580°C.

[0068] In the embodiment of the present application, the cooling adopts concentrated cooling in the front section of cooling, cooling to the coiling temperature, and rapid cooling to the temperature value range, which is conducive to the nucleation of the ferrite phase, while avoiding the formation of pearlite easily due to the high temperature; the formation of martensite and other defects easily due to the low temperature. Exemplarily, the coiling temperature can be 520℃, 540℃, 560℃, 580℃, 600℃, etc.; further, the coiling temperature can be 560℃, 565℃, 570℃, 580℃, etc.

[0069] In some embodiments, the rolling includes rough rolling and finish rolling, wherein the end temperature of the rough rolling is 1050°C to 1100°C, and the end temperature of the finish rolling is 830°C to 900°C.

[0070] In the embodiment of the present application, when the end temperature of rough rolling is too high, acicular ferrite is easily formed with poor plasticity; and when the end temperature of rough rolling is too low, elongated ferrite grains are easily formed or enter the γ+α two-phase region, and thus the end temperature value of the rough rolling is limited. Within the numerical range of the final rolling temperature of the above-mentioned fine rolling, the volume fraction of ferrite in the material structure that meets the requirements can be achieved, and good performance matching can be achieved. Exemplarily, the end temperature of the above-mentioned rough rolling can be 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, etc., and the final rolling temperature of the above-mentioned fine rolling can be 830°C, 840°C, 850°C, 860, 870°C, 880°C, 890°C, 900°C, etc.

[0071] In some embodiments, the heating temperature is 1230°C to 1280°C.

[0072] In the embodiments of the present application, the above heating temperature is limited so that the alloy can be fully melted back while avoiding excessive temperature which may cause severe burning and oxidation. For example, the above heating temperature may be 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, etc.

[0073] In some embodiments, the method further comprises:

[0074] S3, leveling the torsion beam steel, and then pickling it to obtain a finished torsion beam steel; wherein,

[0075] The flattening elongation is 1% to 3%, and the pickled strip steel running speed is 60m / min to 100m / min.

[0076] In the embodiment of the present application, the hot rolled coil is first cooled to room temperature and then flattened, and the flattening elongation is limited to achieve plate shape control and ensure the plasticity of the steel plate. The pickling strip running speed is limited to meet the FB level surface quality requirements of the strip surface. Exemplarily, the flattening elongation can be 1%, 2%, 3%, etc. Exemplarily, the pickling strip running speed can be 60m / min, 70m / min, 80m / min, 90m / min, 100m / min, etc.

[0077] The preparation method of the torsion beam steel is based on the chemical composition of the torsion beam steel. The specific steps of the chemical composition of the torsion beam steel can refer to the above embodiment. Since the preparation method of the torsion beam steel adopts part or all of the technical solutions of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here.

[0078] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:

[0079] 1. By designing the chemical composition of steel and regulating the alloy, the C content is controlled at a lower level while ensuring the strength to ensure the formability and welding performance of the material; through micro-Ti design and the addition of Cr and Mo elements, the dispersion precipitation strengthening effect can be improved on the basis of suppressing the formation of large-sized TiN; by controlling the Mn content, it can effectively play the role of solid solution strengthening and fine grain strengthening; by controlling the S and P content to a lower level, the brittleness of the material is reduced and the formability is improved; by adding V, Mo and other elements, the welding performance and thermal stability of the material are improved, and it is easy to obtain excellent bench fatigue performance of the parts.

[0080] 2. Since the cleanliness of the molten steel is improved by calcium treatment of the molten steel after smelting, and the preparation method of the embodiment of the present application is adopted, the obtained microstructure is ferrite and bainite, the microstructure has good uniformity and small grain size, which can meet the forming welding process in the high-frequency welding pipe making process, and will not cause pipe making or forming cracks due to coarse local structure, poor surface quality, etc., and at the same time improve the inclusion control level, ensuring that the parts have excellent fatigue life.

[0081] 3. By improving the chemical composition of the steel plate and the rolling process, the microstructure of the finished strip steel is ferrite and bainite, which includes granular bainite and lath bainite, with a yield strength of ≥580MPa, a tensile strength of ≥650MPa, an elongation after fracture A80 ≥24%, a hole expansion rate ≥85%, and excellent surface quality and weldability.

[0082] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0083] The embodiment of the present application provides a torsion beam steel. Please refer to the chemical composition of the torsion beam steel shown in Table 1, the microstructure of the torsion beam steel shown in Table 2, the preparation process parameters of the torsion beam steel shown in Table 3, and the performance of the torsion beam steel shown in Table 4.

[0084] Table 1 Chemical composition of torsion beam steel (wt%), the rest is Fe and unavoidable impurities

[0085] serial number C Si Mn Nb Ti Cr Mo Example 1 0.069 0.12 1.52 0.0449 0.056 0.23 0.17 Example 2 0.065 0.11 1.58 0.0374 0.072 0.28 0.12 Example 3 0.076 0.08 1.22 0.0251 0.042 0.37 0.11 Example 4 0.072 0.12 1.65 0.0252 0.042 0.23 0.12 Comparative Example 1 0.032 0.4 1.42 0.035 0.124 0.62 0.0043 Comparative Example 2 0.12 0.2 2.01 0 0.004 0.61 0.14 Comparative Example 3 0.076 0.11 1.66 0.046 0.061 0.45 0.36 serial number V Ca P S [Ti] / [Mo] [Cr]+[Mo] Pc Example 1 0.039 0.003 0.0108 0.001 0.33 0.4 0.176 Example 2 0.036 0.003 0.0102 0.001 0.6 0.4 0.1737 Example 3 0.028 0.002 0.0102 0.001 0.38 0.48 0.168 Example 4 0.022 0.002 0.0102 0.001 0.35 0.35 0.179 Comparative Example 1 0 - 0.0102 0.001 28.833 0.6243 0.147 Comparative Example 2 0.02 0.002 0.0108 0.001 0.028 0.75 0.269 Comparative Example 3 0.022 0.002 0.0102 0.001 0.174 0.81 0.211

[0086] Table 2 Microstructure of steel for torsion beam

[0087]

[0088]

[0089] Table 3 Preparation process parameters of torsion beam steel

[0090] serial number Calcium treatment Heating temperature / ℃ Rough rolling end temperature / ℃ Finishing rolling end temperature / ℃ Coiling temperature / ℃ Example 1 have 1250 1060 890 530 Example 2 have 1250 1070 900 600 Example 3 have 1250 1020 860 580 Example 4 have 1260 1050 880 560 Comparative Example 1 none 1250 1060 840 420 Comparative Example 2 have 1260 1100 880 400 Comparative Example 3 have 1255 1080 880 550

[0091] Table 4 Properties of steel used for torsion beam

[0092] serial number Yield Strength tensile strength Elongation Hole expansion rate Fatigue limit Example 1 623MPa 693MPa 26% 88% 315MPa Example 2 592MPa 656MPa 27.5% 86% 345Mpa Example 3 640MPa 692MPa 24% 93% 330MPa Example 4 664MPa 727MPa 24% 90% 330MPa Comparative Example 1 654MPa 750MPa 18.5% 68% 330MPa Comparative Example 2 743MPa 824MPa 16% 45% 345MPa Comparative Example 3 732MPa 789MPa 16% 62% 315MPa

[0093] In summary, the torsion beam steel provided in the embodiments of the present application has good forming properties, especially outstanding hole expansion performance.

[0094] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A torsion beam steel, characterized in that: The chemical composition of the torsion beam steel includes: C, Si, Mn, P, S, Nb, Ti, Cr, Mo, V, Ca and Fe; among them, in terms of mass fraction, The content of C is 0.05-0.08%, the content of Si is ≤0.15%, the content of Mn is 1.2-1.7%, the content of P is ≤0.015%, the content of S is ≤0.003%, the content of Nb is 0.01-0.05%, the content of Ti is 0.03-0.08%, the content of Cr is 0.1%-0.4%, the content of Mo is 0.1-0.25%, the content of V is 0.01-0.04%, and the content of Ca is 0.0005-0.005%; And satisfying [Ti] / [Mo]≤0.6, [Cr]+[Mo]=0.2~0.5%, Wherein, [Ti] represents the mass fraction of Ti, [Mo] represents the mass fraction of Mo, and [Cr] represents the mass fraction of Cr; The microstructure of the torsion beam steel includes ferrite and bainite, wherein the bainite includes granular bainite and lath bainite, wherein, in terms of area fraction, The content of ferrite is ≥50%, the content of granular bainite is 20% to 35%, and the content of lath bainite is ≤10%.

2. The torsion beam steel according to claim 1, characterized in that: The C content is 0.072% to 0.076%, the Si content is 0.08% to 0.12%, the Mn content is 1.22% to 1.65%, the Nb content is 0.0251% to 0.0252%, the Ti content is 0.042%, the Cr content is 0.23% to 0.37%, the Mo content is 0.11% to 0.12%, the V content is 0.012% to 0.028%, and the Ca content is 0.002%.

3. The torsion beam steel according to claim 1, characterized in that: The welding sensitivity coefficient Pcm≤0.18%.

4. The torsion beam steel according to claim 1, characterized in that: The equivalent grain size in the microstructure is 2.5 μm to 5 μm.

5. The torsion beam steel according to any one of claims 1 to 4, characterized in that: The torsion beam steel meets the following properties: tensile strength ≥ 650 MPa, hole expansion rate λ ≥ 85%, elongation A80 ≥ 24%, and surface quality FB grade.

6. A method for preparing the torsion beam steel according to any one of claims 1 to 5, characterized in that: The method comprises: The molten iron is pre-treated, then smelted, calcium treated and continuously cast to obtain a slab; The slab is heated and rolled, and then cooled and coiled to obtain steel for a torsion beam; wherein the coiling temperature is 520°C to 600°C.

7. The method according to claim 6, characterized in that The coiling temperature is 560°C to 580°C.

8. The method according to claim 6, characterized in that The heating temperature is 1230°C to 1280°C.

9. The method according to claim 6, characterized in that The rolling includes rough rolling and finish rolling, wherein the end temperature of the rough rolling is 1050°C to 1100°C, and the end temperature of the finish rolling is 830°C to 900°C.

10. The method according to claim 6, characterized in that The method further comprises: The torsion beam steel is flattened and then pickled to obtain a torsion beam steel finished product; wherein, The flattening elongation is 1% to 3%, and the pickled strip steel running speed is 60m / min to 100m / min.

Citation Information

Patent Citations

  • High-strength hot rolling automotive frame steel plate and manufacturing method thereof

    CN101565794A

  • Reaming steel and preparation method thereof

    CN116200676A

  • Hot-rolled weather resistant steel product and method of manufacturing the same

    EP4116444A1

  • Cold rolled heat treated steel sheet and a method of manufacturing thereof

    WO2019092576A1